(untitled) (Bangladesh Journal of Psychiatry, 2018)
A boy of 17 years was brought by his parents with the complaints of aggressive, violent and assaultive behavior towards parents, using abusive language, demanding money, restlessness, irritability, irrelevant talk and sleep disturbance. His urine test for cannabinoid was positive. He was diagnosed as substance use disorder and was treated with olanzapine along with psychotherapy. After few days, he developed fever followed by erythematous rash with pruritus and swelling of the face, eyelids, trunk and extremities with raised serum bilirubin, ALT and alkaline phosphatase. He was diagnosed as DRESS (Drug Reaction with Eosinophilia and Systemic Symptoms), a rare complication of olanzapine. This is a dangerous and life threatening adverse effect. Early diagnosis can reduce its morbidity and mortality. Bang J Psychiatry December 2015; 29(2): 64-66